TELECRACY AND ITS INFLUENCE ON PUBLIC CONSCIENCE - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
A social and philosophical analysis is made in the article concerning the influence of public media on public conscience.